2008
DOI: 10.1038/labinvest.3700692
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear defects and hearing loss in mice lacking the collagen receptor DDR1

Abstract: Discoidin domain receptor 1 (DDR1) is a tyrosine kinase receptor that is activated by native collagen. The physiological functions of DDR1 include matrix homeostasis and cell growth, adhesion, branching, and migration, but the specific role of DDR1 in the development and function of the inner ear has not been analyzed. Here, we show that deletion of the DDR1 gene in mouse is associated with a severe decrease in auditory function and substantial structural alterations in the inner ear. Immunohistochemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 48 publications
(54 reference statements)
0
39
1
Order By: Relevance
“…Even though previous studies contradict our finding (6)(7)(8)(9)(10)21,22), these studies nevertheless suggested that the DDR1 gene participates in the development and progression of diseases, such as, auto-inflammatory and renal diseases.…”
Section: ------------------------------------------------------------contrasting
confidence: 56%
See 2 more Smart Citations
“…Even though previous studies contradict our finding (6)(7)(8)(9)(10)21,22), these studies nevertheless suggested that the DDR1 gene participates in the development and progression of diseases, such as, auto-inflammatory and renal diseases.…”
Section: ------------------------------------------------------------contrasting
confidence: 56%
“…DDR1 is a possible susceptibility marker of diseases other than renal diseases, such as schizophrenia, ovarian cancer, juvenile oligoarthritis, hearing loss, Churg-Strauss syndrome, small cell lung carcinoma, and endometrial cancer (6)(7)(8)(9)(10)21,22). Notably, in one study on schizophrenia (9), in which rs1049623 was found to be a susceptibility marker, but this SNP was found to have no significance in the present study.…”
Section: ------------------------------------------------------------mentioning
confidence: 69%
See 1 more Smart Citation
“…This phenotype was associated with abnormalities of the mammary gland epithelium inducing a deficient lactation process [15] . DDR1 KO mice also exhibited abnormalities in the inner ear architecture leading to impaired audition [17] . In kidney, an initial study reported a thickening of the glomerular basement membrane, which did not affect the renal function, since uremia was at the normal range [13] .…”
Section: Physiological Role Of Ddrsmentioning
confidence: 99%
“…A complex between the collagen triple helix and DDR1 functions in mechanotransduction in the inner ear of the mouse auditory system [35]. The ECM rich inner ear provides the mechanical elasticity and rigidity required for the cellular transformation of sound into electrical signals [35][36][37].…”
Section: Discoidin Domain Receptorsmentioning
confidence: 99%